Disentangling loan demand and supply shocks in Russia - Elena Deryugina; Olga Kovalenko; Irina Pantina; Alexey Ponomarenko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
​This article presents three alternative models for decomposing loan developments into components associated with changes in loan demand and supply fundamentals. Two models are based on macro data (error correction model and structural vector autoregression with sign restrictions) and one is based on bank-specific Bank Lending Survey results. We conclude that although loan growth in Russia converges to a long-run equilibrium determined by macroeconomic (demand) factors the convergence is likely to be driven by bank-side (supply) shocks. We identify large and unexplained supply shocks in loan fluctuations during the crisis of 2008–2009, signifying an impairment of credit markets. We also find contractionary shocks unrelated to demand fundamentals or balance sheet structures in 2013, although in general loan developments in 2013 and the first half of 2014 were not at all extraordinary.
URN:NBN:fi:bof-201503111111
Keywords: C32; E51; G21; 330